2002
DOI: 10.1046/j.1464-5491.2002.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subclinical hypothyroidism on metabolic control in children and adolescents with Type 1 diabetes mellitus

Abstract: These data suggest that subclinical hypothyroidism is associated with an increased risk of symptomatic hypoglycaemia. The prompt introduction of substitution therapy is recommended as it reduces its frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 11 publications
(13 reference statements)
2
72
0
8
Order By: Relevance
“…We confirmed this observation in our study: insulin demand was found to be higher in anti-TPO positive group with the presence of low-grade inflammation process. Alternative explanation for our results might be the fact that patients with AITD and DM 1 are more apt to have poorer metabolic control reflected in hypo-and hyperglycaemias due to labile thyroid function [27,29]. Poor metabolic control might contribute to greater insulin demand in such patients.…”
Section: Fig 1 Prevalence Of Anti-tpo According To Tsh After Excludmentioning
confidence: 74%
See 1 more Smart Citation
“…We confirmed this observation in our study: insulin demand was found to be higher in anti-TPO positive group with the presence of low-grade inflammation process. Alternative explanation for our results might be the fact that patients with AITD and DM 1 are more apt to have poorer metabolic control reflected in hypo-and hyperglycaemias due to labile thyroid function [27,29]. Poor metabolic control might contribute to greater insulin demand in such patients.…”
Section: Fig 1 Prevalence Of Anti-tpo According To Tsh After Excludmentioning
confidence: 74%
“…On the other hand, another reason might be the fact that HbA 1c value points only to mean glycaemia value from the previous 3 months, not distinguishing between the actual good metabolic control and significant glycaemic fluctuations. Mohn et al showed [29] that patients with hypothyroidism have more symptomatic hypoglycaemic episodes during 12 months preceding the diagnosis of hypothyroidism which might be the reason for lowering HbA 1c level in patients with poor metabolic control, falsely indicating good metabolic control in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring thyroid autoantibodies is used to identify thyroid autoimmunity, and measurement of TSH may be the most sensitive way to identify patients with thyroid dysfunction (190,194). Subclinical hypothyroidism has been associated with an increased risk of symptomatic hypoglycemia (195) and with reduced linear growth (196). …”
Section: Thyroid Diseasementioning
confidence: 99%
“…From the clinical perspective, patients with epitoperestricted TgAbs will benefit from close monitoring and prompt correction of thyroid dysfunction. It is recognised that undiagnosed thyroid dysfunction in diabetic patients could impair glycaemic control and increase cardiovascular risk through adverse effects on body weight and lipid metabolism (18).…”
Section: Discussionmentioning
confidence: 99%